Innovative Research on the Brand Construction of Five-Color Study Tour in Heilongjiang Province Under the Support and Guidance of Teaching and Research - Feiran Li; Bin Yu (Education Research on Study Tours and Practice, 2026)
Since the implementation of the 14th Five-Year Plan, Heilongjiang Province has thoroughly grasped the core requirements of practical education in the new era. Abandoning the traditional development path that merely pursued scale expansion in the past, the province has taken the systematic restructuring and capacity upgrading of the teaching and research system as a core strategic pivot. It has innovatively established and deeply cultivated the five-color research and study brand system featuring red, green, blue, gold and silver, successfully leading the research and study practice education across the province into a new stage of connotative, standardized and ecological development.This paper systematically sorts out the policy evolution context, multi-subject coordination logic and implementation path of research and study practice education in Heilongjiang Province. It focuses on analyzing a series of key innovations: breaking administrative segmentation and solving coordination barriers through the provincial integrated teaching and research mechanism; reshaping the symbiotic relationship between "travel" and "learning" via a professional curriculum incubator; realizing precise whole-process management of research and study activities and improving service efficiency through a digital governance hub; and expanding the boundary of educational resources by constructing an open collaborative network.